Penerapan E-Learning dengan Aplikasi Zenius untuk Meningkatkan Motivasi Belajar Siswa SMP Negeri 2 Kampar Utara - Nurfitriana Nurfitriana; Zulfah Zulfah (Departement of Mathematics Education, 2020)
This Classroom Action Research aims to increase learning motivation and mastery of E-learning by using the Zenius application in class VIII students of SMP Negeri 2 Kampar Utara in the academic year 2019/2020, totaling 32 people. This research was conducted from the beginning of April 2020 until the end of April 2020. This research is a classroom action research conducted online using several questionnaires, the link of which is sent to students through their WhatsApp group. This online research was conducted because it did not allow the writer to conduct research directly to school because at this time the teaching and learning process was carried out online. This online learning is due to the spread of the COVID-19 corona virus in almost all countries including Indonesia.